Study Quality in Applied Linguistics: Highlights from Dr. Luke Plonsky’s Public Talk - Ashley Beccia; Zhizi (ZZ) Chen (Studies in Applied Linguistics & TESOL)
On October 15, 2024, the Center for International Foreign Language Teacher Education (CIFLTE) hosted a public talk by Dr. Luke Plonsky on study quality, research methods, and ethics in applied linguistics. Faculty and students from universities around the world attended the talk via Zoom.